Sebaran Nilai Daya Hantar Listrik dan Salinitas pada Sumur Gali di Pesisir Pantai Kecamatan Padang Barat - Tivany Edwin; Rinda Andhita Regia; Fauzia Rahmi (Jurnal Dampak, 2018)
This study aims to determine the distribution of electrical conductivity and salinity values in dug well water as an indication of sea water intrusion. The study was conducted on the coastal area of Padang Barat District with 30 sample points and variation of 0-500 m distance from shore to the land. Measurement of electical conductivity values is measured in the field using conductivity meter while for salinity by argentometric method to analyze chloride ions which are then converted to Knudsen Equation. The range of conductivity values is 163.4-5260,8 μS / cm while the salinity value is 0.303-0.564 ‰. The relation of electrical conductivity and salinity values shows a very strong correlation with a value of 0.9373. The relation of the electrical conductivity value with the distance from the shoreline and the depth of the well shows no correlation with values of 0.264 and 0.054. The salinity value with the distance from the shoreline and the depth of the well also showed no correlation with the values of 0.205 and 0.003. The comparison of measured values with groundwater classification known as 2 points is slightly brackish water as an indication of sea water intrusion found in Purus and Berok Nipah sub-districts.